A review of preventing central sleep apnea by inspired CO2. (18th April 2016) - Mulchrone, A; Shokoueinejad, M; Webster, J
Abstract: Although almost completely unknown half a century ago, sleep disorders are gaining recognition as major issues to public health due to their growing prevalence and dire societal consequences. Despite being linked to several infamous catastrophic events such as Chernobyl, it is estimated that 90% of sufferers fail to get diagnosed and receive treatment, and a significant portion of the ones that do are often non-compliant due to the side effects of current treatments. This article presents a review of the current standard treatment for central sleep apnea, and investigates the advantages and possible consequences of using inspired carbon dioxide (CO2 ) as an alternative treatment option.